(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2022)
Abstract: 3D printed, patient-individualized drug-eluting implants for the round window niche (RWN) are an innovative, minimally invasive concept for the medical treatment of inner ear disorders. In this study, we investigate the 3D printing via digital light processing (DLP) and the long-term drug stability of Dexamethasone(DEX)-loaded implant prototypes (storage of 12 months at 25 °C/60 % relative humidity and 40 °C/75 % relative humidity (“accelerated”). A PEGDA-based, DEX-loaded (1 % w/v) photopolymer composition was used. We are able to 3D print 3 x 2.5 x2 mm implant prototypes without the need for a supporting structure. The drug was in accordance with the theoretical drug load as detected via HPLC in fresh 3D printed implant prototypes, so there was no significant drug degradation of DEX during the 3D printing process (duration of time 11 mins). Under the long-term storage conditions approx. 15 % of DEX degradation were detected during 12 months (recovery of DEX 90 % after three months and 85 % after 12 months with 25 °C/60 % relative humidity). Drug degradation increased with “accelerated” storage conditions (recovery of DEX 20 % after 12 months). Where there was a post-curing process (t = 30 mins) via UV light curing oven, it led to a pronounced degradation of DEX (recovery of DEX 80 % recently after manufacturing of implant prototypes with post-curing).